A photon-controlled diode with a new signal-processing behavior. Issue 8 (10th May 2022) - Feng, Shun; Han, Ruyue; Zhang, Lili; Liu, Chi; Li, Bo; Zhu, Honglei; Zhu, Qianbing; Chen, Wei; Cheng, Hui-Ming; Sun, Dong-Ming
Abstract: The photodetector is a key component in optoelectronic integrated circuits. Although there are various device structures and mechanisms, the output current changes either from rectified to fully-on or from fully-off to fully-on after illumination. A device that changes the output current from fully-off to rectified should be possible. We report the first photon-controlled diode based on a n/n − molybdenum disulfide junction. Schottky junctions formed at the cathode and anode either prevent or allow the device to be rectifying, so that the output current of the device changes from fully-off to rectified. By increasing the thickness of the photogating layer, the behavior of the device changes from a photodetector to a multifunctional photomemory with the highest non-volatile responsivity of 4.8 × 10 7 A/W and the longest retention time of 6.5 × 10 6 s reported so far. Furthermore, a 3 × 3 photomemory array without selectors shows no crosstalk between adjacent devices and has optical signal-processing functions including wavelength and power-density selectivity. Abstract : Photon-controlled diodes, as a new circuit element proposed for the first time, change the output current from a fully-off state to a rectified state after illumination, which paves the way for future highly integrated, low-power, intelligent optoelectronic systems.